ADAPTIVE AUTOMATED CONTROL SYSTEM BY THE UNIVERSITY (Journal of Information Technologies in Education (ITE), 2009)
Considered the Automated control system by the university, including subsystems the «Educational and workings plans, graphs of educational process», «Calculation of loading and states», «Partition of load between teachers», «Forming of time-tables», «Controller of employment of audiences and teachers», dean's «Office», «Methodical providing», «Planned – financial department» and other. The questions of adaptation of the educational modules are considered to the features of taught.
Keywords: adaptation; Automated control system by the university; educational modules